الصورة الذهنية للعلاقات العامة في المؤسسات الجزائرية دراسة حالة بجامعة محمد بوضياف ـ المسيلة ـ - ذبيح هاجر; د.حمديني إبتسام (جامعة محمد بوضياف -المسيلة, 2024)
تبحثهذهالدراسةفي الصورةالذهنيةلدىالموظفينبالمؤسساتالجزائريةاتجاهالعلاقاتالعامةبإعتبارأنالعلاقاتالعامةأداةمهمةلنشاطأيمؤسسة،فهيتلعبدورحيوي فيتحسينصورتهاوإظهارهابصورةحسنةلدىجمهورها،وتركأثرطيبلديه.لقدأثارتالدراسةتساؤلرئيسيايتعلقبالبحثفيالتصورالذهنيللجمهورالداخليلجامعةمحمدبوضيافالمسيلة،حولالعلاقاتالعامةوللإجابةعليهإعتمدتعلىالمنهجالوصفيوإتخذتمنإستمارةالإستبيانوسيلةلجمعالمعطياتوتحليلهاموجهةإلىجمهورالمبحوثينفيشكلمجموعةتضم 80 موظف. منأهمالنتائجالتيتوصلتإليهاأنأغلبالعاملينبالجامعةلديهمفكرةعن العلاقاتالعامةولكنعدموجودهيكلتنظيميواضحللعلاقاتالعامةفيالعديدمنالإداراتأدىإلىخلقإدراكمتنوعمنقبلأفرادالعينةللعلاقاتالعامةودورها،وبأنالثقافةالتنظيميةللجامعةلهادوركبيرفيتحديدمدىإهتمامهابالعلاقاتالعامةوهذاالأمريتطلبالتأكيدعلىالقيمالتيتدعمدورالعلاقاتالعامة. This study examines the mental image of employees in Algerian institutions in the direction of Public Relations, considering that public relations is an important tool for the activity of any institution, as it plays a vital role in improving its image and showing it well to its audience, and leaving a good impact on it. The study raised a major question related to researching the mental perception of the internal public of Mohamed Boudiaf Messila University, about public relations, and to answer it, it relied on the descriptive approach and used the questionnaire form as a means of collecting and analyzing data addressed to the audience of respondents in the form of a group of 80 employees. One of the most important findings is that most of the University's employees have an idea about public relations, but the lack of a clear organizational structure for public relations in many departments has led to the creation of a diverse perception by the respondents of public relations and its role, and that the organizational culture of the university has a big role in determining the extent of its interest in public relations, and this requires emphasizing the values that support the role of Public Relations. mental image, Public Relations . :الصورةالذهنية،العلاقاتالعامة .